Progress and Prospects of Sustainable Aviation Fuel Implementation: A Critical Analysis, Challenges and Conclusions - Sergii Boichenko; Oleksandr Bavykin; Artem Artyukhov; Sylwester Bogacki; Marek Rutkowski; Dariusz Reśko (Energies, 2025)
Modern aviation is one of the main consumers of petroleum-based fuels, consuming nearly 100 million gallons of fuel per year, and this consumption continues to grow. On the other hand, airlines have committed to achieving net-zero carbon dioxide (CO2) emissions in the industry by 2050. Fulfilling this commitment necessitates the investigation of new and the optimization of existing processes for the production of alternative, renewable, and environmentally safe feedstocks. This article was prepared as part of the research project “Development of Technological Solutions for Obtaining Composite Motor Fuels from Secondary Raw Materials to Enhance Energy Security”.